2006
DOI: 10.2485/jhtb.15.82
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Peri-implant Bone Defects with Different Bone Grafts and Guided Bone Regeneration:

Abstract: Objective; The present investigation was designed to evaluate the regenerating effects of chip bone grafts harvested from implant drilling and biomaterials with or without combined application of guided bone regeneration (GBR) for the augmentation of peri-implant bone defects. Materials and methods; Four mongrel dogs were used. After the mandibular premolars were extracted for 12 weeks, surgical implantation of 4 titanium implants was performed on each side of the mandible. Chip bone was collected during the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Large amount of experiments and clinical research have shown that Bio-Oss have a similar surface area and poriness with human cancellous bone, providing framework for regeneration of new bone tissue 20) . The organic composition in Bio-Oss is removed in the process of preparation so as to reduce the risk of rejection 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Large amount of experiments and clinical research have shown that Bio-Oss have a similar surface area and poriness with human cancellous bone, providing framework for regeneration of new bone tissue 20) . The organic composition in Bio-Oss is removed in the process of preparation so as to reduce the risk of rejection 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Immediate bone augmentation using the Ti membrane after infected tooth extraction is found to be feasible and safe. To prevent the early exposure, early bone augmentation after extraction of infected teeth and extensive bone loss is successfully achieved by using a Ti barrier membrane accompanied by socket filling with autologous platelet-rich fibrin (PRF) or bone graft material [15,16]. The Ti membranes are more difficult to insert than flexible membranes due to sharp edges [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of studies are controversial and the effectiveness of stiff membranes is debated. Zhong et al did not find any benefit in application of titanium membranes, and interestingly, they observed that the membrane may even decrease the quantity of regenerated bone (12).…”
Section: Non-absorbale Barrier Membranesmentioning
confidence: 97%